2013
DOI: 10.7763/ijcte.2013.v5.761
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Engergy Consumption in Programs Using Cohesion Technique

Abstract: Abstract-The objective of this work is to reduce energy consumption of source programs written in C. The underlying technique employs code transformation which focuses on cohesion. Four classes of transformations will be considered: function, loop optimization, control structure, and operator. Code transformation is evaluated by effectiveness, efficiency, space complexity, number of instructions executed, number of pages, size of memory page allocated, and energy consumption. The results suggest that different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…In general, neither of the approaches provides significant reduction in energy consumption. For instance in [11] authors concluded that by applying the static approach using the cohesion technique, and in [13] authors aim at finding patterns that would result in minimal energy consumption that could be used during code generation. Moreover, the dynamic approach is questionable in safety-critical real-time systems, where predictability is the key characteristic of the system.…”
Section: Greening Software Executionmentioning
confidence: 99%
“…In general, neither of the approaches provides significant reduction in energy consumption. For instance in [11] authors concluded that by applying the static approach using the cohesion technique, and in [13] authors aim at finding patterns that would result in minimal energy consumption that could be used during code generation. Moreover, the dynamic approach is questionable in safety-critical real-time systems, where predictability is the key characteristic of the system.…”
Section: Greening Software Executionmentioning
confidence: 99%